TANTANGAN DAN PELUANG PARIWISATA BERBASIS MASYARAKAT DI ERA NEW NORMAL - Ertien Rining Nawangsari; Leily Suci Rahmatin (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2021)
This paper is compiled to analyze the opportunities and challenges of community-based tourism, in facing the adaptation of a new life in the midst of the Covid-19 pandemic, tourism potential which is the capital for tourism development and the participation of local communities as the stakeholders main tourism. The choice of research focuses on community participation in tourism, especially in the new normal era due to tourism activities where all activities are carried out by prioritizing the movement from the area of origin to the destination area, making tourism an activity that is vulnerable to the spread of covid - 19. The main challenge in tourism today is more to the level of public awareness of health protocols, opportunities that greatly support Tamansari Tourism Village in the form of a variety of tourist attractions in one tourism destination. The research method approach used is descriptive qualitative research instruments with in-depth interviews, documentation study and involved observation. Tourism in the new normal era is expected to be able to adapt CHSE Cleanliness, Health, Safety, and Environmental Sustainability in order to maintain tourists' confidence in tourist attraction in reducing covid-19 transmission.Keywords: Community Participation, Tourism Village, CHSE